HAMBATAN LITERASI DALAM PEMECAHAN SOAL CERITA MATEMATIKA DI MI AL HIKMAH 1 SUKONATAR - Fals Aldino; Putri Maja Mulia Kulzum; Mahrus Hadi (Penerbit Widina, Widina Media Utama, 2026)
This study aims to delineate the cognitive obstacles of Madrasah Ibtidaiyah students in solving mathematical word problems triggered by low reading literacy. Employing a qualitative descriptive approach, this research involved three fifth-grade students from MI Al Hikmah 1, selected through purposive sampling based on high, moderate, and low Mathematical Initial Ability (MIA) categories. Data were collected via numeracy literacy tests and interviews, followed by analysis through data reduction, data display, and conclusion drawing. The findings reveal significant variations in cognitive obstacles: students in the low category exhibit